Menjembatani Kesenjangan Kognitif: Integrasi Jurnal Reflektif dan Collaborative Sharing untuk Meningkatkan Keterampilan Pemecahan Masalah IPA Fisika pada Mahasiswa Calon Guru Sekolah Dasar yang Heterogen - Abtokhi, Ahmad; Admoko, Setyo (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Academic heterogeneity among prospective elementary school teachers (PGSD/MI) often precipitates cognitive gaps in physics learning. A critical deficiency regarding Problem Solving Skills (PSS) is the students' inability to transform visual representations of problems into mathematical formulations, despite comprehending the narrative context. This study evaluates the effectiveness of integrating Reflective Journals and Collaborative Sharing to enhance PSS based on Docktor’s five indicators (Useful Description, Physics Approach, Specific Application, Mathematical Procedures, and Logical Progression) in the topic of motion dynamics. Involving 18 students from diverse academic backgrounds (natural sciences, social sciences, religious studies, and vocational schools), the intervention utilized independent logic scaffolding and peer procedural validation. Test results indicated a significant improvement, with average scores rising from 1.39 (Very Low) to 3.65 (Good). Specific findings revealed that reflective journals effectively restructured physics logic, while collaborative sharing corrected calculation inaccuracies—a persistent weakness among students from non-science backgrounds. Demonstrating the strategy's efficacy in bridging competency gaps, this study recommends developing a systematic learning model that integrates these two strategies to optimize and sustain students' PSS.